Outsourcing security private military contractors and U.S. foreign policy - Stanley, Bruce E. (Bruce Edwin) (Potomac Books, an imprint of the University of Nebraska Press, 2015)
The use of private security contractors by the United States is not a recent phenomenon. In a post-Vietnam world, as political leaders reduce their nations' military force structure, they face conflicts beyond their anticipated scope and duration.